2021
DOI: 10.1111/ene.15198
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and atrial fibrillation: a systematic review

Abstract: Background and purpose Patients with migraine are at increased risk of stroke. The aim was to systematically review the current literature on the association between migraine and atrial fibrillation, which is a relevant risk factor for stroke. Methods PubMed was searched for ‘migraine’ AND ‘atrial fibrillation’ and selected original investigations on the association of migraine and atrial fibrillation for our analysis. Articles without original data, such as guidelines, narrative reviews, editorials and others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…MwA doubles the risk of stroke, and especially in the young there is a strong association between MwA and stroke even in the absence of vascular risk factors ( 12 , 13 ). Whether the doubling of stroke risk is due to primary MwA or due to a disorder causing secondary MwA and stroke is unknown ( 12 , 14 , 15 ). In addition, there is an association of MwA and patent foramen ovale (PFO), and in patients with cryptogenic stroke who have migraine, there is a high prevalence of PFO (79%) with right-to-left shunt ( 12 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…MwA doubles the risk of stroke, and especially in the young there is a strong association between MwA and stroke even in the absence of vascular risk factors ( 12 , 13 ). Whether the doubling of stroke risk is due to primary MwA or due to a disorder causing secondary MwA and stroke is unknown ( 12 , 14 , 15 ). In addition, there is an association of MwA and patent foramen ovale (PFO), and in patients with cryptogenic stroke who have migraine, there is a high prevalence of PFO (79%) with right-to-left shunt ( 12 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Available evidence suggests 2fold increased risk of stroke among patients with migraine [7,8], and recurrence of stroke in young populations [9]. Studies including a recent meta-analysis demonstrated greater risk particularly in individuals aged less than 45 years, women with migraine with aura (MA), oral contraceptive users, and smokers [8, 10,11]. A recent follow-up study from South Korea that included individuals aged > 40 years also showed 35% greater risk among migraineurs [12].…”
Section: Introductionmentioning
confidence: 99%
“…4 Third, the complex association between atrial fibrillation and migraine has been a little oversimplified not covering issues, such as hypercoagulability, antithrombotics as migraine prevention therapy, and others. 5…”
mentioning
confidence: 99%
“…4 Finally, we recognize that the relationship between atrial fibrillation and migraine with aura is complex and can be either direct or indirect. 5 However, our review focused on microembolism and its role in migraine and stroke pathophysiology. Other associations between cardiac arrhythmias and stroke risk in patients with migraine were beyond this Review's scope.…”
mentioning
confidence: 99%